2019
DOI: 10.1021/acs.jafc.9b00037
|View full text |Cite
|
Sign up to set email alerts
|

Rhein from Rheum rhabarbarum Inhibits Hydrogen-Peroxide-Induced Oxidative Stress in Intestinal Epithelial Cells Partly through PI3K/Akt-Mediated Nrf2/HO-1 Pathways

Abstract: Rheum rhabarbarum has been widely used as a herbal medicine and food in China. The objective of this study was to investigate the cytoprotective action and underlying mechanisms of rhein, one active ingredient isolated from R. rhabarbarum, on H2O2-challenged rat small intestine epithelial cells (IEC-6 cells). H2O2-challenged IEC-6 cells were incubated in the pretreatment with or without rhein or LY294002, a PI3K/Akt inhibitor. The cell viability, apoptosis, intracellular reactive oxygen species (ROS), and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 49 publications
4
45
0
Order By: Relevance
“…It is well established that H2O2 could be used to stimulate oxidative stress in vitro [30][31][32]. In the present study, we found that treatment with 400 μM H2O2 resulted in decreased cell viability in HTR8/SVneo cells, which is consistent with a previous study [1].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is well established that H2O2 could be used to stimulate oxidative stress in vitro [30][31][32]. In the present study, we found that treatment with 400 μM H2O2 resulted in decreased cell viability in HTR8/SVneo cells, which is consistent with a previous study [1].…”
Section: Discussionsupporting
confidence: 93%
“…The transcription of HO-1 and NQO1, the downstream genes of Nrf2, are primarily under the control of Nrf2 in maintaining cell redox balance [49,50]. Under oxidative stress, Nrf2 could translocate into the nucleus to activate the expression of its downstream antioxidant enzymes [32]. Similar with the previous studies, the Nrf2 signaling was activated by H 2 O 2 treatment in order to compensate for the oxidative damage [32,51].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The increased nuclear NRF2 fluorescence intensity in IPEC-1 cells subjected to H 2 O 2 in the current study was therefore a cellular defense response. Recently, Zhuang et al [49] also reported that H 2 O 2 induces a translocation of NRF2 to the nuclei in rat small intestine epithelial cells. Contradictory with the increase in the nuclear NRF2 accumulation, the mRNA expression of NQO1 and SOD1 was downregulated in IPEC-1 cells during oxidative stress, and this may be due to cell antioxidant system failure.…”
Section: Discussionmentioning
confidence: 97%
“…Oxidative stress, arising from the excessive generation of reactive oxygen species (ROS) and imbalances in the antioxidant system, can damage multiple cellular components through DNA hydroxylation, protein denaturation, lipid peroxidation, and membrane rupture. This outcome leads to apoptosis and other modes of cell death [4,5]. Given the small intestine of calf gastrointestinal hypoplasia, oxidative stress can disrupt the integrity and functioning of calf intestinal epithelial cells, thereby affecting absorption and allowing pathogen invasion and disease [6].…”
Section: Introductionmentioning
confidence: 99%